Beyond rivalry : psychology and theology as complements - Craddock, Alan Edward (Sutherland, N.S.W. : Hillfort Resources, 2001)
Describes amd applies a constructive form of relationship between the disciples of Christian theology and psychology.
Relationships between psychology and theology -- Attitudes, towards self and the grace of God -- Pastoral counselling, facilitating insight -- Leadership in the church -- Leadership in the family.
Includes bibliographical references and index.
Keywords: Psychology, Religious; Psychology; Theology